Flow-based stress-blended eddy simulation: A local RANS/LES turbulence model for urban flow CFD simulations - Léo Cotteleer; Riccardo Longo; Frédéric Debaste; Alessandro Parente (Results in Engineering, 2024)
In the present article, we introduce a local hybrid RANS/LES turbulence model, the Flow-based Stress-Blended Eddy Simulation (Fb-SBES). The methodology is applied to urban flow simulations in atmospheric boundary layer. The blending from RANS to LES is performed on the fly with respect to a flow deviation parameter. This makes the model self-adaptive and requires no prior knowledge of the flow contrary to typical zonal LES models. The present methodology enables the RANS equations to be solved in the major part of the computational domain (e.g. on average 88% for a single building). The RANS zone is modelled with a comprehensive RANS turbulence model for ABL simulations that sustains the fully developed inlet conditions until the built environment. In general, Fb-SBES shows better agreement with experimental data on the building and in the wake compared to advanced RANS and DDES simulations.